Investigating The Use of Knowledge Assessment Rubrics in Vocational Schools in Mathematics Learning - Harsela, K; Herman, T (International Conference on Elementary Education, 2020)
A rubric is an alternative assessment tool needed by teachers in determining student learning processes. As a guide to assessment, the rubric aims to equalize evaluators’ perceptions and minimize subjectivity. This study aims: (1) to investigate the extent to which assessment rubrics on knowledge aspects are applied in mathematics teaching and learning activities in vocational schools, and (2) to examine the obstacles faced by teachers in the use of knowledge assessment rubrics. This type of research is a qualitative descriptive study, with the research subjects being two teachers of mathematics studies in one of the vocational schools in Dayeuhkolot, Kabupaten Bandung. The methods were to use interview and documentation of data collection in the form of lesson plan that used by the teacher when teaching. The results of the study show that: (1) the use of knowledge assessment rubric at the level of the vocational school is still not well implemented and is also not optimal; and (2) obstacles faced by teachers in the use of knowledge assessment rubrics, namely: a) teachers still find it difficult to make knowledge assessment rubrics, and b) teachers argue that the process of creating knowledge assessment rubrics takes a lot of time